Generation Mean Analysis in Physio-morphic Traits of Aerobic Rice in Assam, India - , Hrishikesh Ojah, P. Talukdar, Rumjhum Phukan, D. Sarma, Nabajyoti Bhuyan, Shazmira Zaman (Archives of Current Research International, 2024)
An experiment was carried out to study the genetic architecture of few physio-morphic quantitative traits of rice under aerobic condition. Generation mean analysis was carried out in three selected crosses viz.Banglami/Luit, Koimurali/Luit and Guni/Gopinath, involving six generations (P1, P2, F1, F2, BC1 and BC2) at the experimental farm of SCS college of Agriculture, Assam Agricultural University, Dhubri, Assam, India during 2017 and 2018. The individual scaling tests were used to test the adequacy of additive dominance model. The gene effects were estimated using three parameter models (joint scaling test) suggested by Cavalli (1952) and six parameter model suggested by Haymen (1958). The analysis of variance among different generations of different crosses revealed significant variation for most of the characters indicating considerable variability in the material studied. All the characters except height growth rate in cross II, recorded significance for at least one of the four individual scaling tests in all the 3 crosses. Estimation of different gene effects and their interactions were done in OPSTAT software. Significant positive additive effects were recorded for plant height and height growth rate for in all the three crosses. Preponderance of dominance effect in the expression of height growth rate, spikelet fertility, grain yield, harvest index, root weight and root shoot ratio was evident from the significant positive dominance (h) effect in all the three crosses. With respect to interaction effects, all the characters except height growth rate in cross II, exhibited significant interaction effect for one or more epistatic interactions i.e.[i], [j] or [l] in all the three crosses studied. It is evident that for all the yield and other adaptive traits, additive, dominance and interaction effects were present indicating the complex inheritance of the traits under aerobic condition. Hence, focus should be on improving individual characters separately based on the nature of gene action.